Critical perspective on infodemic and infodemic management in previous Ebola outbreaks in Uganda - Obol, Sunday Jimmy; Nzedibe, Okechi (Frontiers in Public Health, 2024)
This research investigates the complex dynamics of Uganda’s recent Ebola outbreaks, emphasizing the interplay between disease spread, misinformation, and existing societal vulnerabilities. Highlighting poverty as a core element, it delves into how socioeconomic factors exacerbate health crises. The study scrutinizes the role of political economy, medical pluralism, health systems, and informal networks in spreading misinformation, further complicating response efforts. Through a comprehensive analysis, this study aims to shed light on the multifaceted challenges faced in combating epidemics in resource-limited settings. It calls for integrated strategies that address not only the biological aspects of the disease but also the socioeconomic and informational ecosystems that influence public health outcomes. This perspective research contributes to a better understanding of how poverty, medical pluralism, political economy, misinformation, and health emergencies intersect, offering insights for future preparedness and response initiatives.